4th booster-dose SARS-CoV-2 heterologous and homologous vaccination in rheumatological patients - Gallardo-Nelson, Maria Jose; Cruces, Marcos; Gómez, Yolanda M.; Fuenzalida, Constanza; Silva, Javiera; Aravena-Traipi, Laura; Nuñez, Eduardo; Gaete-Angel, Aracelly; Rivas-Yañez, Elizabeth; Kalergis, Alexis M.; Soto-Rifo, Ricardo; Valiente-Echeverria, Fernando (Frontiers in Immunology, 2024)
Objective to evaluate the immune response to the SARS-CoV-2 vaccines in adults with immune-mediated rheumatic diseases (IMRDs) in comparison to healthy individuals, observed 1-20 weeks following the fourth vaccine dose. Additionally, to evaluate the impact of immunosuppressive therapies, vaccination schedules, the time interval between vaccination and sample collection on the vaccine’s immune response. Methods We designed a longitudinal observational study conducted at the rheumatology department of Hospital de Copiapó. Neutralizing antibodies (Nabs) titers against the Wuhan and Omicron variant were analyzed between 1-20 weeks after administration of the fourth dose of the SARS-CoV-2 vaccine to 341 participants (218 IMRD patients and 123 healthy controls). 218 IMRD patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), systemic vasculitis (VS) and systemic scleroderma (SS) were analyzed. Results Performing a comparison between the variants, Wuhan vs Omicron, we noticed that there were significant differences (p<0.05) in the level of the ID50, both for healthy controls and for patients with IMRDs. The humoral response of patients with IMRDs is significantly lower compared to healthy controls for the Omicron variant of SARS-CoV-2 (p = 0.0015). The humoral response of patients with IMRDs decreases significantly when the time interval between vaccination and sample collection is greater than 35 days. This difference was observed in the response, both for the Wuhan variant and for the Omicron variant. Conclusion The IMRDs patients, the humoral response variation in the SARS-CoV-2 vaccine depends on doses and type of vaccine administered, the humoral response times and the treatment that these patients are receiving.